Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's simplify the given expression step by step:
[tex]\[ \frac{16 \times 2^{n+1} - 4 \times 2^n}{16 \times 2^{n+2} - 2 \times 2^{n+2}} \][/tex]
### Step 1: Simplify the Numerator
First, we simplify the numerator, which is [tex]\( 16 \times 2^{n+1} - 4 \times 2^n \)[/tex].
1. Recall the property of exponents: [tex]\( a \times 2^b = 2^{b+\log_2a} \)[/tex].
2. Rewrite [tex]\( 16 \times 2^{n+1}\)[/tex]:
[tex]\[ 16 = 2^4 \implies 16 \times 2^{n+1} = 2^4 \times 2^{n+1} = 2^{4+n+1} = 2^{n+5} \][/tex]
3. Rewrite [tex]\( 4 \times 2^n \)[/tex]:
[tex]\[ 4 = 2^2 \implies 4 \times 2^n = 2^2 \times 2^n = 2^{n+2} \][/tex]
4. Substitute these back into the numerator:
[tex]\[ 2^{n+5} - 2^{n+2} \][/tex]
### Step 2: Factor the Numerator
Factor out the common term [tex]\( 2^{n+2} \)[/tex]:
[tex]\[ 2^{n+2}(2^3 - 1) \quad \text{(since \( 2^{n+5} = 2^{n+2+3} = 2^{n+2} \times 2^3\))} \][/tex]
[tex]\[ 2^{n+2}(8 - 1) = 2^{n+2} \times 7 \][/tex]
So, the simplified numerator is [tex]\( 7 \times 2^{n+2} \)[/tex].
### Step 3: Simplify the Denominator
Now, simplify the denominator, which is [tex]\( 16 \times 2^{n+2} - 2 \times 2^{n+2} \)[/tex].
1. Rewrite [tex]\( 16 \times 2^{n+2} \)[/tex]:
[tex]\[ 16 = 2^4 \implies 16 \times 2^{n+2} = 2^4 \times 2^{n+2} = 2^{n+4+2} = 2^{n+6} \][/tex]
2. Rewrite [tex]\( 2 \times 2^{n+2} \)[/tex]:
[tex]\[ 2 \times 2^{n+2} = 2^1 \times 2^{n+2} = 2^{1+n+2} = 2^{n+3} \][/tex]
3. Substitute these into the denominator:
[tex]\[ 2^{n+6} - 2^{n+3} \][/tex]
### Step 4: Factor the Denominator
Factor out the common term [tex]\( 2^{n+3} \)[/tex]:
[tex]\[ 2^{n+3}(2^3 - 1) \quad \text{(since \( 2^{n+6} = 2^{3+n+3} = 2^{n+3} \times 2^3 \))} \][/tex]
[tex]\[ 2^{n+3}(8 - 1) = 2^{n+3} \times 7 \][/tex]
So, the simplified denominator is [tex]\( 7 \times 2^{n+3} \)[/tex].
### Step 5: Simplify the Whole Fraction
Now, let's combine the simplified numerator and denominator:
[tex]\[ \frac{7 \times 2^{n+2}}{7 \times 2^{n+3}} \][/tex]
Cancel out the common factors [tex]\( 7 \times 2^{n+2} \)[/tex] in the numerator and denominator:
[tex]\[ \frac{1}{2} = 0.5 \][/tex]
Thus, the original expression simplifies to:
[tex]\[ \frac{16 \times 2^{n+1} - 4 \times 2^n}{16 \times 2^{n+2} - 2 \times 2^{n+2}} = 0.5 \][/tex]
The values for the numerator and denominator are [tex]\( 28 \)[/tex] and [tex]\( 56 \)[/tex], respectively, giving results:
[tex]\[ (28, 56, 0.5) \][/tex]
[tex]\[ \frac{16 \times 2^{n+1} - 4 \times 2^n}{16 \times 2^{n+2} - 2 \times 2^{n+2}} \][/tex]
### Step 1: Simplify the Numerator
First, we simplify the numerator, which is [tex]\( 16 \times 2^{n+1} - 4 \times 2^n \)[/tex].
1. Recall the property of exponents: [tex]\( a \times 2^b = 2^{b+\log_2a} \)[/tex].
2. Rewrite [tex]\( 16 \times 2^{n+1}\)[/tex]:
[tex]\[ 16 = 2^4 \implies 16 \times 2^{n+1} = 2^4 \times 2^{n+1} = 2^{4+n+1} = 2^{n+5} \][/tex]
3. Rewrite [tex]\( 4 \times 2^n \)[/tex]:
[tex]\[ 4 = 2^2 \implies 4 \times 2^n = 2^2 \times 2^n = 2^{n+2} \][/tex]
4. Substitute these back into the numerator:
[tex]\[ 2^{n+5} - 2^{n+2} \][/tex]
### Step 2: Factor the Numerator
Factor out the common term [tex]\( 2^{n+2} \)[/tex]:
[tex]\[ 2^{n+2}(2^3 - 1) \quad \text{(since \( 2^{n+5} = 2^{n+2+3} = 2^{n+2} \times 2^3\))} \][/tex]
[tex]\[ 2^{n+2}(8 - 1) = 2^{n+2} \times 7 \][/tex]
So, the simplified numerator is [tex]\( 7 \times 2^{n+2} \)[/tex].
### Step 3: Simplify the Denominator
Now, simplify the denominator, which is [tex]\( 16 \times 2^{n+2} - 2 \times 2^{n+2} \)[/tex].
1. Rewrite [tex]\( 16 \times 2^{n+2} \)[/tex]:
[tex]\[ 16 = 2^4 \implies 16 \times 2^{n+2} = 2^4 \times 2^{n+2} = 2^{n+4+2} = 2^{n+6} \][/tex]
2. Rewrite [tex]\( 2 \times 2^{n+2} \)[/tex]:
[tex]\[ 2 \times 2^{n+2} = 2^1 \times 2^{n+2} = 2^{1+n+2} = 2^{n+3} \][/tex]
3. Substitute these into the denominator:
[tex]\[ 2^{n+6} - 2^{n+3} \][/tex]
### Step 4: Factor the Denominator
Factor out the common term [tex]\( 2^{n+3} \)[/tex]:
[tex]\[ 2^{n+3}(2^3 - 1) \quad \text{(since \( 2^{n+6} = 2^{3+n+3} = 2^{n+3} \times 2^3 \))} \][/tex]
[tex]\[ 2^{n+3}(8 - 1) = 2^{n+3} \times 7 \][/tex]
So, the simplified denominator is [tex]\( 7 \times 2^{n+3} \)[/tex].
### Step 5: Simplify the Whole Fraction
Now, let's combine the simplified numerator and denominator:
[tex]\[ \frac{7 \times 2^{n+2}}{7 \times 2^{n+3}} \][/tex]
Cancel out the common factors [tex]\( 7 \times 2^{n+2} \)[/tex] in the numerator and denominator:
[tex]\[ \frac{1}{2} = 0.5 \][/tex]
Thus, the original expression simplifies to:
[tex]\[ \frac{16 \times 2^{n+1} - 4 \times 2^n}{16 \times 2^{n+2} - 2 \times 2^{n+2}} = 0.5 \][/tex]
The values for the numerator and denominator are [tex]\( 28 \)[/tex] and [tex]\( 56 \)[/tex], respectively, giving results:
[tex]\[ (28, 56, 0.5) \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.